Pemanfaatan Media Daur Ulang Sampah Plastik dalam Meningkatkan Kesadaran di Lingkungan MI Salafiyah Syafi’iyah Ajung Jember - Alika Nur Azizah; Muhammad Suwignyo Prayogo; Eka Sintia Rahmawati; Siti Iltimah Romadonia (Jurnal Cakrawala Pendidikan dan Biologi, 2026)
. This research is driven by the low literacy of plastic waste management in primary education, where students tend to perceive cleanliness only as disposing of trash without having the skills for reuse. This study aims to describe the utilization of recycled plastic waste media in enhancing students' environmental awareness at MI Salafiyah Syafi’iyah through an experiential learning approach. The method employed is descriptive-analytical qualitative, with data collection techniques including direct observation, interviews, and documentation. The research implementation was carried out through three main stages: participatory waste sorting, selection of clothing pattern designs as adhesive media, and the construction of creative collages into an educational display board named "Karyaku." The results indicate that the integration of plastic waste as a learning medium is capable of transforming students' paradigms from a consumptive to a creative perspective, as well as improving their practical understanding of the 3R principles (Reduce, Reuse, Recycle). The success of this research is evidenced by the creation of aesthetic and functional visual media that not only enhances students' creativity but also fosters a sense of responsibility and sustainable environmental concern for the school ecosystem.